K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

16 tháng 8 2018

Ta có: \(\left(x^3-x^2\right)^2-4x^2+8x-4=0\)

\(\Rightarrow\left(x^3-x^2\right)^2-\left(4x^2-8x+4\right)=0\)

\(\Rightarrow\left(x^3-x^2\right)^2-\left(2x-2\right)^2=0\)

\(\Rightarrow\left(x^3-x^2+2x-2\right)\left(x^3-x^2-2x+2\right)=0\)

\(\Rightarrow\left(x^2+1\right)\left(x-1\right)\left(x^2-2\right)\left(x-1\right)=0\)

\(\Rightarrow\left(x^2+1\right)\left(x-1\right)^2\left(x^2-2\right)=0\Rightarrow\orbr{\begin{cases}x-1=0\\x^2-2=0\end{cases}}\)\(\Rightarrow\orbr{\begin{cases}x=1\\x=\sqrt{2}orx=-\sqrt{2}\end{cases}}\)

Vậy x=1 hoặc \(x=\sqrt{2}\)hoặc x = \(-\sqrt{2}\)

16 tháng 8 2018

http://123link.pro/eP1KS

16 tháng 8 2018

vô dây hộ mk , mk vừa làm  h đỡ viết , cx câu b ý

https://olm.vn/hoi-dap/question/1289396.html